EVALUATION OF HANDLING OF B3 LOADING (DANGEROUS AND TOXIC GOODS) ON SHIPS AT SEI SELARI FERRY PORT - Surnata, Surnata; Triwahyuni, Siti Nurlaili; Agustini, Elfita; Qussay, Agni (IWTJ : International Water Transport Journal, 2024)
in accordance with KP-DRJD 539 of 2022 concerning Guidelines for Planning, Development and Performance Evaluation of River, Lake and Ferry Ports, it is worthy of evaluation in order to determine the extent of operational performance that has been implemented so far. The purpose of this study is to determine the performance weight of the Kuala Tungkal Ferry Port. In this study, the researcher used a quantitative research method, namely collecting and processing figures that have been obtained through surveys. Based on the results of the study, it is known that the Kuala Tungkal Ferry Port has worked with an assessment weight of 76.7 and the category "Good" refers to KP-DRJD 539 of 2022 concerning Guidelines for Planning, Development and Performance Evaluation of River, Lake and Ferry Ports. This can be seen from the recorded ship maneuver time of 7 minutes and a rating of 80, the average time for vehicles to board and disembark the ship recorded at 25 seconds and 2 minutes 48 seconds with a rating of 100 and 80, the vehicle queue time to board the ship recorded at 12 hours 46 minutes and a rating of 20, and the pier usage ratio which received a score of 100. Thus, several actions are needed to improve the operational performance of the Kuala Tungkal Ferry Port such as ship traffic control by the LPS (Local Port Service) so that optimal ship maneuver time can be implemented. In addition, to optimize vehicle queue time, it is necessary to provide an appeal to the public to obey the rules in force in the Kuala Tungkal Ferry Port environment.